2007
DOI: 10.1007/s11626-007-9052-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated glucose levels on interactions of cardiac fibroblasts with the extracellular matrix

Abstract: Exposure of fibroblasts to high glucose levels promotes a fibrotic response characterized by increased expression of extracellular matrix components including interstitial collagens. Little is known about the effects of glucose levels on other aspects of fibroblast function. Fibroblasts in the myocardium are surrounded by an extensive extracellular matrix composed predominantly of type I collagen. Interactions between fibroblasts and the myocardial extracellular matrix are thought to affect heart function by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 47 publications
7
23
0
Order By: Relevance
“…VICs are similar to those observed with cardiac fibroblasts, in which increased gel contraction was observed with an increase in glucose concentration from 1 to 4.5 g l 21 [22].…”
supporting
confidence: 83%
See 1 more Smart Citation
“…VICs are similar to those observed with cardiac fibroblasts, in which increased gel contraction was observed with an increase in glucose concentration from 1 to 4.5 g l 21 [22].…”
supporting
confidence: 83%
“…Because prior work with cardiac fibroblasts suggested that culture pre-treatment can increase cell contraction of collagen gels [22], cells were starved from glucose and pyruvate 24 h prior to gel preparation by replacing the medium with a (2glucose, 2pyruvate, þglutamine) DMEM solution containing 10% BGS, 1% antibiotic -antimycotic and 1% HEPES. Although our initial studies showed that depriving VICs of glucose for 24 h before collagen gel preparation did not appear to affect their collagen gel contraction behaviour, the withholding of glucose and pyruvate was performed prior to all experiments to avoid confounding results because those factors were being investigated.…”
Section: Glucose Starvation Pre-treatmentmentioning
confidence: 99%
“…Collagen types I and III potently promoted CF migration, and plating on the collagen substrates had an equal additive effect on the hyperglycemia-induced CF migration. In contrast, neonatal fibroblasts plated on type I collagen and cultured in hyperglycemic media migrated slower than in normo-glycemic media (Zhang et al, 2007). This could be due to differences in the origin of fibroblasts and the type of migration assays i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are several reports describing in vitro effects of glucose concentration on CF function [13][14][15][16], the diabetic milieu is far more complex than hyperglycaemia alone and other factors such as hyperlipidaemia, advanced glycation end products, oxidative stress, proinflammatory cytokines, adipokines and profibrotic cytokines must also be considered [31].…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports describing in vitro effects of elevated glucose concentration on CF function [13][14][15][16], however hyperglycaemia represents only one component of the complex diabetic milieu. Very recent evidence from rat and mouse models of T2DM has suggested that there are functional differences in CF derived from T2DM hearts compared with control hearts [17,18], however there is no current evidence that such differences exist in human CF.…”
Section: Introductionmentioning
confidence: 99%